Capturing Legionella pneumophila effector enzymes using a ubiquitin derived photo-activatable probe - Kloet, Max S.; van der Heden van Noort, Gerbrand J. (Frontiers in Molecular Biosciences, 2024)
Upon infection of host cells the Legionella pneumophila bacterium releases a multitude of effector enzymes into the host's cytoplasm that manipulate cellular host pathways, including the hostubiquitination pathways. The effectors belonging to the SidE-family are involved in non-canonical phosphoribosyl serine ubiquitination (PR-ubiquitination) of host substrate proteins. This results in the recruitment of ER-remodeling proteins and the formation of a Legionella-containing vacuole which is crucial in the onset of legionnaires disease. PR-ubiquitination is a dynamic process reversed by other Legionella effectors called Dups. During PR-Ubiquitin phosphodiester hydrolysis Dups form a covalent intermediate with the phosphoribosyl ubiquitylated protein using its active site His67 residue.We envisioned that covalent probes to target Legionella effectors could be of value to study these effectors and contribute to deciphering the complex biology of Legionella infection. Hence we effectively installed a photo-activatable pyridinium warhead on the 5'-OH of triazole-linked ribosylated ubiquitin allowing crosslinking of the probe to the catalytic histidine residues in Legionella SidE or Dup enzymes. In vitro tests on recombinantly expressed DupA and SdeAPDE revealed that the probe was able to capture the enzymes covalently upon photo-activation.